MUSCLE INJURY AND SPORTS REHABILITATION MANAGEMENT IN ENDURANCE TRAINING ORIENTED TO WINTER SPORTS - Wang,Zhihong (2023)
ABSTRACT Introduction: Muscle injury in ski sports training has gradually increased, greatly impairing performance in ice and snow sports competitions. Objective: To study muscle injury and muscle movement during ice and snow sports training and the rehabilitation of muscle injuries. Methods: Thirty skiers with knee muscle injuries were selected as subjects and underwent rehabilitation training for six weeks, and the indicators were statistically evaluated. Results: The ski injuries were mainly muscle strain, muscle or ligament strain, and ligament rupture. The indices after treatment were significantly different from those before treatment (P < 0.05); compared with the three rehabilitation programs, the improvement of each index in group C was significantly different from that in the other two groups (P < 0.05), while there was no significant difference in the improvement of each index between the multi-angle isometric training treatment in group A and the proprioceptive neuromuscular stimulation technique in group B (P>0.05). Conclusion: The influence of recovery training technology on knee muscle re-education was proposed, and a rehabilitation plan for skiing was presented. Level of evidence II; Therapeutic studies - investigation of treatment outcomes.